PATTERNS OF DUCTILE DEFORMATION IN ATTICO-CYCLADIC MASSIF - Spanos, D.; Koukouvelas, I.; Kokkalas, S.; Xypolias, P. (Bulletin of the Geological Society of Greece, 2010)
The area of Lavrion constitutes the westernmost part of the Attico-Cycladic massif where the allochthonous Cycladic Greenschist-Blueschist unit overthrusts the para-authochthonous Basal unit. The tectonic contact of these units forms a crustal scale thrust zone which is the continuation of the Evia thrust. Our research was focused on quartz-rich schists of the overlying allochthonous unit. Combination of microstructural, finite strain data and quartz and calcite c-axis fabrics analysis was used to characterize the kinematics of rock flow within the thrust zone. The latter was formed under conditions of progressive exhumation and decompression of the high-pressure schists of the AtticoCycladic massif. A dominant top-to-the-ENE sense of shearing along the thrust zone is inferred by several shear sense criteria. The analysis of several specimens collected from various structural depths manifest that the deformation close to the thrust zone occurred under approximately plane strain conditions and was characterized by an Rxz strain ratio which fluctuates between 3 and 6.5.